An audit of Irish mental health law for compliance with international human rights norms in respect of seven categories of 'mental health rights claims' : positive and negative findings, and recommendations for reform - Quirke, Edel Thérèse (Trinity College (Dublin, Ireland). School of Law, 2011)
This thesis subjects the legal regulation of the civil mental health law regime in Ireland to a ‘human rights audit’ subsequent to the implementation of the Mental Health Act 2001 (MHA 2001). The following structure is adopted: -- 1. In the Introduction, an explanation of the categories of ‘mental health rights’ standards chosen for the performance of the human rights audit of Irish mental health law is performed. -- 2. Chapter 1 provides an account of the legal structure of the provision of mental health care in Ireland, including an outline of the health system and a description of the evolution of mental health regulation culminating in a detailed explanation of the mental health law regime as established under the MHA 2001. -- 3. In Chapter 2, an explanation of the structure of the major international human rights protection bodies, and a detailed evaluation of the human rights standards established at an international level that are of importance to people who have mental health disabilities, is provided. -- 4. In Chapter 3, the human rights protections provided by the Irish Constitution to people who engage with the mental health law regime is assessed, including an analysis of the impact of the European Convention on Human Rights Act 2003 on the constitutional jurisprudence in the area of mental health. -- 5. Chapter 4 contains an account of the mental health law systems in England (with whom Ireland shares a common legal heritage and a shared membership of the Council of Europe) and in South Africa (which has unique constitutional provisions providing protection for a socio-economic right to health, and a mental health law regime that differs to the Irish system in a number of interesting respects). -- 6. In Chapter 5, the extent to which Irish constitutional, legislative, and common law provisions succeed in meeting the standards established by the international human rights provisions, and whether those international human rights provisions have in legal outcomes provided for meaningfial substantive protections for mental health patients in Ireland, is evaluated. -- 7. Finally, the conclusions drawn are summarised at the end of the work, together with recommendations for the reform of Irish mental health law to improve the level of protection of the international human rights ‘mental health claims’ provided.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin